2021
DOI: 10.3390/cancers13081894
|View full text |Cite
|
Sign up to set email alerts
|

The Screen Project: Guided Direct-To-Consumer Genetic Testing for Breast Cancer Susceptibility in Canada

Abstract: There is limited information of the outcomes of direct-to-consumer testing for BRCA1 and BRCA2 mutations. The Screen Project was initiated in 2017 to offer BRCA1 and BRCA2 genetic screening to all Canadians over the age of 18 who wish to know their mutation status. Patients enrolled in the study from 2017 to 2019 and were followed for one year after the receipt of a genetic test result. Study subjects registered online and were sent a saliva sample kit, which was shipped to the reference laboratory. Pre-test g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…High uptake of direct-to-consumer genetic testing demonstrates high general interest; however, products through private ancestry/health companies are neither clinical nor diagnostic. Pricing of private clinical testing at $200–400 US is expensive for most individuals [ 44 , 53 ].…”
Section: Results Of Panel Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High uptake of direct-to-consumer genetic testing demonstrates high general interest; however, products through private ancestry/health companies are neither clinical nor diagnostic. Pricing of private clinical testing at $200–400 US is expensive for most individuals [ 44 , 53 ].…”
Section: Results Of Panel Discussionmentioning
confidence: 99%
“…Studies implementing versions of genetic population-based testing in various countries have demonstrated that wide-scale implementation can provide cancer prevention without adversely affecting participants (select studies listed in Table 1 ). Population-based BRCA testing can identify carriers of HCS in individuals with previous cancer diagnosis [ 39 ], those of Ashkenazi Jewish descent [ 7 , 40 , 41 , 42 ], and in the general population [ 8 , 9 , 43 , 44 ]. While BRCA1 and BRCA2 are the most well-studied genes, inclusion of other HCS genes will improve cancer risk prediction [ 8 , 9 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies evaluating population-based models have found that population-based testing identifies carriers that would be missed by traditional criteria, does not result in increased psychosocial concerns, can result in clinically actionable information, and can be cost-effective if implemented at 30 years old or earlier ( 52 , 54 56 ). In population testing, genetic counseling is generally reserved for the post-test setting for those identified with positive results (i.e., pathogenic variants), similar to providing specialized counseling for an individual with high cholesterol on routine screening.…”
Section: Population-based Testing As the Future Of Preventative Medicinementioning
confidence: 99%
“…18 Furthermore, we support consumer-based models of testing such as the Screen Project in Canada, whereby testing is made available to all Canadians on a pay-for-service basis, with extensive follow-up for individuals identified to carry a pathogenic variant. 19 It is important that after a positive genetic test, women are provided with up-to-date and accurate information regarding cancer risk and preventive measures. It may be helpful to use the graphs provided here to communicate risk profiles under various scenarios.…”
Section: F I G U R Ementioning
confidence: 99%